Common variants in IL-17A/IL-17RA axis contribute to predisposition to and progression of congestive heart failure. Issue 27 (July 2016) - Sandip, Chaugai; Tan, Lun; Huang, Jin; Li, Qing; Ni, Li; Cianflone, Katherine; Wang, Dao Wen
Abstract : Abstract: Heart failure is characterized by immune activation leading to production and release of proinflammatory cytokines. Interleukin 17A (IL-17A) is a proinflammatory cytokine and multiple lines of evidence from animal and human studies suggest crucial roles of IL-17A in heart failure. Therefore, we investigated whether common polymorphisms of genes IL17A and IL17RA (coding interleukin 17 receptor A) contribute to genetic predisposition to heart failure and adverse clinical outcomes associated with it. A total of 1713 adult patients with congestive heart failure and 1713 age- and sex-matched controls were genotyped for promoter single nucleotide polymorphisms (SNPs), rs2275913 and rs8193037 in IL17A and rs4819554 in IL17RA, to assess the relationship between individual SNPs and the risk of congestive heart failure. Results showed that rs8193037 in IL17A was associated with the risk of congestive heart failure (odds ratio [OR] = 0.76; 95% confidence interval [CI] 0.63–0.90, adjusted P = 0.002) after adjustment for multiple cardiovascular risk factors including age, sex, smoking status, diabetes, hypertension, and dyslipidemia. This association was evident in both ischemic and nonischemic heart failure ( P = 0.005 and P = 0.05, respectively). Furthermore, prospective follow-up of 12.7 months for the occurrence of adverse clinical outcomes showed that rs4819554 in IL17RA was significantly associated with cardiovascular mortality (hazard ratio [HR] = 1.28; 95% CI = 1.02–1.59, adjusted P = 0.03) after adjustments for multiple cardiovascular risk factors and New York Heart Association functional class. This study demonstrated associations of rs8193037 in the promoter of IL17A with the risk of congestive heart failure, and of rs4819554 in the promoter of IL17RA with the risk of cardiovascular mortality in patients with congestive heart failure. These data lend further support to the notion that immune activation and genetic polymorphisms contribute to heart failure pathogenesis and progression. Abstract : Supplemental Digital Content is available in the text